2019
DOI: 10.1038/s41598-019-55259-8
|View full text |Cite|
|
Sign up to set email alerts
|

Asthma and/or hay fever as predictors of fertility/impaired fecundity in U.S. women: National Survey of Family Growth

Abstract: This study addresses whether asthma and/or hay fever predict fertility and impaired fecundity. The lifetime number of pregnancies (fertility) and spontaneous pregnancy losses (impaired fecundity) in 10,847 women representative of the U.S. population 15 to 44 years of age with histories of diagnosed asthma and/or hay fever are analyzed in the 1995 National Survey of Family Growth using multivariable Poisson regression with multiple covariates and adjustments for complex sampling. Smokers have significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 139 publications
(162 reference statements)
3
11
0
1
Order By: Relevance
“…[14][15][16] However, the age of the patients with respiratory allergies was even higher, which has also been reported in other studies, 4,17 suggesting a possible influence of allergy in women's fertility. 1,10 Likewise the data reflected the increase in maternal age at the first pregnancy during the study period, 10,14 showing that in Spain in 2000 the mean age was 30.74 years and in 2018 it was 32.2 years. 14 Regarding allergic comorbidities, drug allergy was by far the most prevalent, as shown in other studies.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…[14][15][16] However, the age of the patients with respiratory allergies was even higher, which has also been reported in other studies, 4,17 suggesting a possible influence of allergy in women's fertility. 1,10 Likewise the data reflected the increase in maternal age at the first pregnancy during the study period, 10,14 showing that in Spain in 2000 the mean age was 30.74 years and in 2018 it was 32.2 years. 14 Regarding allergic comorbidities, drug allergy was by far the most prevalent, as shown in other studies.…”
Section: Discussionmentioning
confidence: 93%
“…1 As PTD and intrauterine growth restriction have been associated with a predominance of Th1 profile, 1 some authors have suggested that a deviation from a Th2 response may be the key for these adverse pregnancy outcomes to develop. 1,10 Asthma has been well studied, 3 but other atopic comorbidities are overlooked in our daily practice, and little is known about the possible effects of these conditions on pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proinflammatory T2-low asthma endotype has similar biomarker characteristics to the fetal-maternal interface during implantation. Prior to implantation and in the peri-implantation period the fetal–maternal interface is also characterized by immune deviation to a proinflammatory and T2-low endotype [ 14 ]. The same mechanism underlying the T2-low asthma and miscarriage explained the high incidence of miscarriage in asthmatic women.…”
Section: Discussionmentioning
confidence: 99%